Constitutional politics in Canada and the United States - Newman, Stephen L. (State University of New York Press, 2004)
The Canadian constitutional reforms of 1982, which included a Charter of Rights and Freedoms analogous to the American Bill of Rights, brought about a convergence with American constitutional law. As in the U.S., Canadian courts have shown themselves highly protective of individual rights, and they have not been shy about assuming a leading and sometimes controversial political role in striking down legislation. In clear and easy-to-understand language, the contributors not only chart, but also explore, the reasons for areas of similarity and difference in the constitutional politics of Canada and the United States. Book jacket.
Keywords: Constitutional law -- Canada.; Civil rights -- Canada.; Judicial review -- Canada.; Constitutional law -- United States.; Civil rights -- United States.; Judicial review -- United States.; Droit constitutionnel -- Canada.; Droits de l'homme -- Canada.; Contrôle juridictionnel des lois -- Canada.; Droit constitutionnel -- États-Unis.; Droits de l'homme -- États-Unis.; Contrôle juridictionnel des lois -- États-Unis.; LAW -- Constitutional.; LAW -- Public.; Civil rights; Constitutional law; Judicial review; Canada; United States